The Characteristics of Non-Litigation Resolution for Life Insurance Lawsuit in Indonesia - HUDA, Mokhamad Khoirul; HERNOKO, Agus Yudha; KHAIRANDY, Ridwan (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).12, 2018)
This study analyzed the characteristics of non-litigation resolution for life insurance lawsuit in Indonesia. The result found that the non-litigation solution for life insurance lawsuit in Indonesia must be through Department of Mediation and Arbitration of Insurance (in Indonesia, known as BMAI). When the mediation -as the legal action from a costumer- was objected, the lawsuit would proceed to the adjudication. When the customer won on this adjudication level, the insurance company was then obligated to do some payment as mentioned on the insurance policy. Furthermore, when the legal action of a customer was objected, the customer was then free to do an arbitrage legal action. The arbitration was final and had fixed legal power. Thus, any appeal, cassation, or judicial review could not be held. The solution for life insurance lawsuit through BMAI has several characteristics such as quick in procedures, dynamic, innovative, cheap, and low budget. In addition, the dispute solution through BMAI is confidential, quick in time, and supported by some experts on related types of lawsuit, thus, it may result in fair judgment.